Was the future built or destroyed since the time of Palma? - Gonzales del Valle Solis, Angélica María (2019)
This article will analyze the tradition «¡Beba, padre, que le da la vida!...», a text where Ricardo Palma makes reference to the feminine role in issues considered masculine, as it used to happen with civil engineering. Even though job vacancies in the construction sector were usually occupied by men, since it was considered that their performance was more efficient, gradually these positions have been occupied by women. These women have become empowered and currently occupy high hierarchy and responsibility positions, leading both building sites and their own construction companies in an optimal way.